SOCIOECONOMIC AND SOCIOBEHAVIOURAL INFLUENCES ON RESILIENCE AND VULNERABILITY - Cosco, T.D. (Innov Aging, 2017)
When presented with challenges that accompany ageing, such as reduced physical capability, some individuals respond more positively than others, maintaining higher levels of wellbeing than expected, i.e. they are resilient. Although socioeconomic advantage is positively associated with individual (internal) and external resources that promote resilience in some contexts, the relationship between socioeconomic position (SEP) and resilience as defined above is not known. We sought to examine the relationships of SEP, assessed by participants’ occupational class, and sociobehavioral factors with mental wellbeing for a given physical capability. Participant data at age 60–64 came from the MRC National Survey of Health and Development, a nationally representative British birth cohort study (n=1756). Resilience was operationalised as having a greater than expected level of wellbeing, captured by the Warwick-Edinburgh Mental Well-being Scale (WEMWBS), for a given level of performance-based physical capability, assessed using grip strength, chair rise, standing balance, and timed-up-and-go tests. The degree of resilience or vulnerability was quantified as the difference between observed and expected WEMWBS scores, i.e. residual values, for physical capability using linear regression; positive residual scores indicated resilience and negative residual scores indicated vulnerability. The relationship between SEP, physical activity and social support, and the resilience-vulnerability score was examined in sex-adjusted linear regression models. Individuals with higher occupational class, physical activity and social support had higher scores on the resilience-vulnerability scale. These relationships need to be considered when identifying targets for interventions promoting wellbeing in populations experiencing age-related functional decline.